2010
DOI: 10.1007/s11738-010-0469-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide protects soybean seedlings against drought-induced oxidative stress

Abstract: Increasing evidence indicates that hydrogen sulfide (H 2 S) is the third ''gas signal molecule'' after NO and CO in animal. In the present study, we found that soybean (Glycine max L.) seedlings sprayed with exogenous H 2 S donor NaHS prolonged the longer survival time of life, and enlarged higher biomass of both leaf and root than in non-sprayed controls under continuous drought stress. With the continuous drought stress, the content of chlorophyll in the leaves of both Xu-1 and Xu-6 cultivar of soybean decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 40 publications
4
76
0
Order By: Relevance
“…Meanwhile, the study of Li et al shows that spraying NaHS improves heat tolerance in maize by alleviating the increase of electrolyte leakage and MDA [39]. In addition, Zhang and his colleagues indicate that spraying NaHS delays excessive accumulation of MDA and reactive oxygen species, but enhance SOD activity against cooper stress and droughtinduced oxidative stress in wheat seeds and soybean seedlings [11,15]. All these findings suggest that H 2 S possibly use the similar mechanism to resist various stresses in different plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the study of Li et al shows that spraying NaHS improves heat tolerance in maize by alleviating the increase of electrolyte leakage and MDA [39]. In addition, Zhang and his colleagues indicate that spraying NaHS delays excessive accumulation of MDA and reactive oxygen species, but enhance SOD activity against cooper stress and droughtinduced oxidative stress in wheat seeds and soybean seedlings [11,15]. All these findings suggest that H 2 S possibly use the similar mechanism to resist various stresses in different plants.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that H 2 S is involved not only in plant responses to drought and copper stresses but also in tolerance to salinity, heat, cadmium, boron and chromium stresses [6][7][8][9][10]. It is reported that exogenous H 2 S can enhance the resistance of plants to drought stress [11][12][13][14] and copper stress [15,16] by improving the activities of antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD). However, whether endogenous H 2 S is involved in plant cold stress response is poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies concerning H 2 S emission in plants were associated with the plant response to pathogens as part of a so-called Sulfur Induced Resistance (Bloem et al, 2004). Using a H 2 S-releasing compound, H 2 S was later reported to confer a protective effect against oxidative (Zhang et al, 2009b(Zhang et al, , 2010b and cadmium (Sun et al, 2013) stresses, alleviate aluminum toxicity (Zhang et al, 2010c), increase antioxidant activity, and participate in root organogenesis (Zhang et al, 2009a). Several independent groups have recently reported the participation of H 2 S in ABA-and ethylene-dependent stomatal closure induction (García-Mata and Lamattina, 2010;Liu et al, 2011Liu et al, , 2012Jin et al, 2013).…”
mentioning
confidence: 99%
“…One of the most Environment restricting factors negatively affecting plant growth in the majority of the world's agricultural lands could be defined as a drought stress (Tas and Tas, 2007), and greatly limits crop production worldwide (Zhang et al, 2010). As a common consequence of drought stress, the production of reactive oxygen species (ROS), such as superoxide radical (O 2-), hydrogen peroxide (H 2 O 2 ), and hydroxyl radical (OH) is increased (Valentovic et al, 2006) which is due to the enhanced leakage of electrons to molecular oxygen (Arora et al, 2002).…”
Section: Introductionmentioning
confidence: 99%